Modern trends in research on steel, aluminium and composite structures : proceedings of the XIV International Conference on Metal Structures (ICMS2021), Poznan, Poland, 16-18 June 2021 /: proceedings of the XIV International Conference on Metal Structures (ICMS2021), Poznan, Poland, 16-18 June 2021. (2021) - Unknown
No abstract available